Deeply buried clastic rock diagenesis evolution mechanism of Dongdaohaizi sag in the center of Junggar fault basin, Northwest China - Guo Shasha; Zhang Xuecai; Wang Jue; Wang Siwen; Liu Kemin; Wang Jinkai (Open Geosciences)
To reveal the diagenetic sequence of reservoir rocks in the central part of the deep depression basin, the Wuerhe Formation in Junggar Basin was taken as an example to conduct the detailed studies on its sedimentary facies, diagenetic sequence, and the micropore structure evolution rules based on the comprehensive data from a super deep exploration well C-6 (approximately 7,000 m in depth). First, an arid environment fan delta sedimentary model of the Wuerhe Formation was established, and its sedimentary evolution law was clarified as a gradual transition from a fan delta front to a fan delta plain during the water-regression process until the lake dried up. Then, the diagenesis types and evolution sequence of the Wuerhe Formation, and the influence degrees of the compaction, cementation, and dissolution on the rock formation process were clarified. Finally, the diagenesis and pore evolution model was established, and the greatest impact factors of the late reservoir densification were clarified. Based on this research, the diagenesis and pore evolution processes of the deep rocks in the studied deep central sag were ultimately revealed to provide useful guidance for the deeply buried oil and gas reservoir exploration.